2015
DOI: 10.1128/aac.04082-14
|View full text |Cite|
|
Sign up to set email alerts
|

Clostridium difficile Isolates with High Linezolid MICs Harbor the Multiresistance Gene cfr

Abstract: We studied the molecular mechanisms of linezolid resistance in 9 isolates of toxigenic Clostridium difficile with high linezolid MICs. The activity of linezolid was determined against 891 clinical isolates of toxigenic C. difficile. The MIC 50 and MIC 90 of linezolid were 0.75 g/ml and 1.5 g/ml, respectively. Nine strains (1%) showed high linezolid MICs (6 g/ml to 16 g/ml) and also were resistant to clindamycin, erythromycin, and chloramphenicol. These strains were selected for molecular studies: sequencing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 22 publications
2
57
0
Order By: Relevance
“…Recently, Marin et al (124) reported reduced susceptibility to linezolid (MIC, 6 to 16 mg/liter) in 9/891 clinical isolates of C. difficile. These 9 strains belonged to RT001, RT017, and RT078, and they all possessed the cfr gene, which showed 100% sequence identity with a fragment of Tn6218 (124).…”
Section: Transposable Elementsmentioning
confidence: 99%
“…Recently, Marin et al (124) reported reduced susceptibility to linezolid (MIC, 6 to 16 mg/liter) in 9/891 clinical isolates of C. difficile. These 9 strains belonged to RT001, RT017, and RT078, and they all possessed the cfr gene, which showed 100% sequence identity with a fragment of Tn6218 (124).…”
Section: Transposable Elementsmentioning
confidence: 99%
“…Two other LZD-resistant clinical isolates, A-1290 and A-1291, did not have any mutations in L3 but contained a Val88Ile variation in ribosomal protein L20 (rplT; CD630_06870), just as was seen with resistant isolates A-1410 and A-1412. No mutations were found in any of the copies for the 23S rRNA PTC loop of domain V that correspond to the ones described in LZD-resistant S. aureus isolates (14), and no mutations were found in the topoisomerase II genes (DNA gyrase) in any of the clones selected with CDZ.…”
Section: Resultsmentioning
confidence: 93%
“…Marín et al had identified a cfr-like gene in the majority of clinical isolates with elevated LZD MICs (14). Sequencing of the amplified cfr fragments showed 2 different profiles with a 2-bp difference (GenBank sequence accession numbers KM359438 and KM359439).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations